A Descriptive Analysis of Urinary ESBL-Producing-Escherichia coli in Cerdanya Hospital - Lorena Patrícia Gaviria; Lourdes Montsant; Carlos Azuaje; Aida González-Díaz; Juan P. Horcajada; Enric Limón; Miguel Viñas; Paula Espinal; Ester Fusté (Microorganisms, 2022)
Urinary tract infections caused by extended-spectrum β-lactamase Escherichia coli (ESBL-EC) are increasing worldwide and are a current concern because treatment options are often limited. This study investigated antimicrobial susceptibility, antimicrobial resistance genes (ARGs), and the biological diversity of urinary ESBL-EC isolates at Cerdanya Hospital, a European cross-border hospital that combines French and Spanish healthcare models. Bacterial identification and susceptibility were determined using the Microscan WalkAway® system and ESBL production was examined by the double-disk synergy method. Isolates were sequenced using the Ion S5™ next-generation sequencing system, with the whole-genome sequences then assembled using SPADEs software and analyzed using PubMLST, ResFinder, FimTyper, PlasmidFinder, and VirulenceFinder. A phylogenetic analysis was performed by constructing an assembly-based core-SNV alignment, followed by a phylogenetic tree constructed using Parsnp from the Harvest suite. All isolates studied were multidrug-resistant and could be classified into 19 different sequence types characterized by a high genetic diversity. The most prevalent ESBL-enzymes were CTX-M-14 and CTX-M-15. High-risk international clones (ST131, ST10, and ST405) were also identified. The results demonstrated the absence of a single predominant clone of ESBL-MDR-EC at Cerdanya Hospital.